Experiences with Google Approval Process: an automated approach to enhancing efficiency in Android releases - Andrade, Ewerton; Sousa, Janislley; Lopes, Matheus; Barbosa, Davi; Lima, Wesllen; Lacerda, Jimmy (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2024: Anais do IX Simpósio Brasileiro de Testes de Software Sistemático e Automatizado, 2024)
Google enforces a licensing requirement for Original Equipment Manufacturers (OEM) to market Android-powered mobile devices with Google Mobile Services (GMS) and to perform Firmware-Over-the-Air (FOTA) updates. This certification process is known as the Google Approval Process (GAP). Due to the potential for this process to be time-consuming and costly, it is common to implement strategies aimed at reducing failures and resource wastage. In this context, this paper presents the approach adopted by our institute to enhance its efficiency on GAP. Through the implementation of this approach, the following results were achieved: (I) a decrease of up to 92% in Android software release drops (an avg of ∼55% compared to 2022); (II) a reduction of up to 86% in processing time (an avg of ∼22% compared to 2022); and (III) an increase in fixed Common Vulnerabilities and Exposures (CVEs) over the years.